(untitled) (Comprehensive Journal of Science, 2026)
This study investigates how Artificial Intelligence (AI) can improve English vocabulary acquisition among university students at the Faculty of Languages, University of Benghazi, Libya. Using a true-experimental design, 60 English as a Foreign Language (EFL) students in their first semester were randomly assigned to two groups. The experimental group used the Duolingo app for vocabulary learning, while the control group received traditional instruction. Data analysis were conducted using SPSS, employing methods such as T-tests, and ANCOVA. Results indicated that students who used Duolingo significantly outperformed those in the control group in vocabulary acquisition. The study concludes by recommending the incorporation of AI-driven platforms like Duolingo into EFL curricula and suggests further research to assess their long-term impact on language learning.